VOCATIONALIZATION OF INDIAN EDUCATION: EMERGING PERSPECTIVES - Dr. Namita Sahoo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Many Commissions and committees have constantly recommended that education at various level should provide vocational education with the objective of employment. Vocationalization education at school stage has its origin in 28th century when Sadler commission, known as Calcutta University Commission 1917-19 suggested the introduction of 10+2 pattern. The need of vocational education was felt more after the independence by many educationists and experts of our country. The NaiTalim system of education proposed by Mahatma Gandhi with the aim on self-reliance and work education was emphasized in the curriculum. In the report of Mudaliar commission 1956 craft centered education with multipurpose school system was recommended. The Calcutta commission report was also recommended that after completing class 10th students should be education with productivity and national development. After the impact of Russian Education system many work experience curriculum was introduced at school stage. One of the most important thing come into focused in the Ishwar Bhai Patel Committee report 1978 suggested about social useful productive work (SUPW) a modified version of work experience. The growing unemployment problem among school students requires a rethinking of the total vocational education system. The present paper will focus on problems of vocationalization of education and its future perspectives.